2004
DOI: 10.1080/01443610410001685493
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of insulin lispro given before or after meals in pregnant women with Type 1 diabetes—the effect on glycaemic excursion

Abstract: In order to study the glucose excursion associated with pre- and postprandial administration a randomised controlled trial with patients randomised to receive insulin lispro (IL) immediately before or after a standardised meal was performed. Pregnant women with diabetes who were treated with IL as part of a basal bolus regime were asked to bring their own usual lunch and administer their own IL. Maternal glycaemia was monitored preprandially and then at 15-minute intervals for 3 hours following the first bite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Short-acting insulin can be used to aggressively control postprandial glucose. Lispro insulin can be used in diabetic pregnancies [346,347]. There is no increase in congenital anomaly rates in pregnancies where lispro insulin is used [348].…”
Section: Pregnancy As the Prototype For Targeting Ppgmentioning
confidence: 99%
“…Short-acting insulin can be used to aggressively control postprandial glucose. Lispro insulin can be used in diabetic pregnancies [346,347]. There is no increase in congenital anomaly rates in pregnancies where lispro insulin is used [348].…”
Section: Pregnancy As the Prototype For Targeting Ppgmentioning
confidence: 99%
“…The results of the systematic review are shown in Figure S1. Of the 1475 potentially relevant studies, 67 16,17,23–87 fulfilled the inclusion criteria (Table 1). Two hundred and ten outcomes were extracted from the studies.…”
Section: Resultsmentioning
confidence: 99%
“…The safety and efficacy of Insulin lispro was shown in some trials, and in some case reports performed with pregnant women with gestational diabetes (22,23,25) and type 1 diabetes (24,26,27,(29)(30)(31)(32). It was also found not to cross the placenta (36).…”
Section: Insulin Lispromentioning
confidence: 98%
“…Finally, it should be stated that many studies and case reports, most of them with small number of patients, have been conducted with the rapid-acting ana-logues lispro and aspart, which have shown to be safe and effective in the treatment of pregnant women with gestational and type 1 diabetes (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Table 1 shows the results of fourteen articles reporting on 2,069 pregnant diabetic women, 1,794 with type 1 diabetes, and 275 cases of gestational diabetes.…”
Section: Insulin Glulisinementioning
confidence: 99%